Disposition and metabolism of [14C]-galunisertib, a TGF-βRI kinase/ALK5 inhibitor, following oral administration in healthy subjects and mechanistic prediction of the effect of itraconazole on galunisertib pharmacokinetics. (3rd April 2018) - Cassidy, Kenneth C.; Gueorguieva, Ivelina; Miles, Colin; Rehmel, Jessica; Yi, Ping; Ehlhardt, William J.
Abstract: 1. The disposition and metabolism of galunisertib (LY2157299 monohydrate, a TGF-βRI Kinase/ALK5 Inhibitor) was characterized following a single oral dose of 150 mg of [ 14 C]-galunisertib (100 µCi) to six healthy human subjects. 2. The galunisertib plasma half-life was 8.6 h, while the 14 C half-life was 10.0 h. Galunisertib was abundant in circulation (40.3% of the 14 C AUC024 h), with 7 additional metabolites detected in plasma. Two metabolites LSN3199597 (M5, mono-oxidation), and M4 (glucuronide of M3) were the most abundant circulating metabolites (10.7 and 9.0% of the 14C AUC024 h respectively). The pharmacological activity of LSN3199597 was tested and found to be significantly less potent than galunisertib. 3. The dose was recovered in feces (64.5%) and in urine (36.8%). Galunisertib was cleared primarily by metabolism, based on low recovery of parent in excreta (13.0% of dose). Due to the slow in vitro metabolism of galunisertib in suspended hepatocytes, a long term hepatocyte system was used to model the human excretion profile. 4. Expressed cytochromes P450 and hepatocytes indicated clearance was primarily CYP3A4-mediated. Mechanistic static modeling that incorporated small non-CYP-mediated metabolic clearance and renal clearance components predicted an AUC ratio of 4.7 for the effect of itraconazole, a strong CYP3A4 inhibitor, on galunisertib.